MODELING TABAT EFFECT INUNDATION IN THE PEAT SWAMP FOREST CENTRAL KALIMANTAN - Petrisly Perkasa (Jurnal Teknologi Berkelanjutan, 2013)
Peat swamp forests serve as an abundant water catchment area in rainy season and then releases it gradually in dry season. The main function of peat swamp forests are as the hydrology regulator in an ecosystem, and the function will be disrupted when the peat swamp forests have excessive drainage condition. Recently, the peat swamp forests of Central Kalimantan are badly damaged by prolonged exploration without any responsibility to preserve it. One of the damage causes of the peat swamp forests in Central Kalimantan are many canals made when illegal loggers get their harvested wood out to the estuary of nearest watershed. Therefore, it forms canals that drain water with no control. The effect is peat swamp forests will be very dry and trigger devastating fire that cannot be extinguished in a short time. One of the efforts to deal with the problem is by recovering the hydrology condition of peat swamp forests ecosystem through duct insulation using simple dam locally called “tabat”. The making of tabat is easily designed in order that the implementation is not very hard, and the material selection such as forest wood dominate the construction because the wood will be cracked gradually without disturbing the ecosystem process and restoration principle in peat swamp forests. This study was one of the efforts to rescue peat swamp forests by hydrology restoration using a modeling concept with a computer software of hydraulics. The modeling concept used steady flow water surface profile to find out the capacity of cross section to designed flood. After the simulation, tabat modeling was then made to the height of canal. The modeling process resulted in the width of inundation in tabat. The height of water level and the number of tabat were required to optimally inundate the research area. The modeling result by a computer software of hydraulics shows the increase of water level in canals at 15 to 30 cm and the width of inundation in tabat when the designed flood of two-year return period was modeled to 280.67 km2 and for the period of five years was 306.04 km2 from the target of hydrology restoration of 250 km2. The modeling of inundation width in tabat of peat swamp forests will be suggestion for the government of Central Kalimantan Province and the stakeholders in building a big scale tabat.